Exploring Fasting In Christianity And Islam - Andi Alfian (Jurnal Studi Agama, 2022)
Fasting is one of the religious practices or rituals or worship that can be found in almost every religious tradition, including the Christian and Islamic religious traditions. Several scholars of religious studies, through various research, claim that fasting has been practiced thousands of years ago by various religious adherents in the world and persists to this day. This study attempts to describe the teachings and practices of fasting in Christianity and Islam and then provides an analysis of the similarities and differences in the implementation of these teachings in the context of Indonesia. This study is library research in the sense that this study will rely on books and scientific journals related to this topic as primary data sources. This study found that the practice of fasting in Christianity and Islam each has its meaning and has its uniqueness, and characteristics. For example, they have their meaning about the purpose of fasting, the arguments they use for fasting, the types of fasting, and the procedures for fasting. This study argues that religious teachings, both Christianity and Islam, are dynamic, multi-interpretative, and contextual by exploring these issues.